DEVELOPMENT OF A WEB-BASED GEOGRAPHIC INFORMATION SYSTEM (GIS) FOR DISASTER RISK MANAGEMENT IN MALAYSIA - M. Khairi Mahyudin (CV. Fahr Publishing, 2024)
Gaps in access to spatial data and digital tools continue to hinder disaster risk management systems in Malaysia, particularly at the community level. This study aims to design and develop a web-based Geographic Information System (GIS) that serves as a decision-support tool for disaster response and preparedness. Using a Design Science Research (DSR) methodology, the system was built through stages of needs assessment, participatory design, open-source modular development, and both qualitative and quantitative evaluation. The results show high usability scores (average SUS >80), an average system response time of 1.2 seconds, and stable performance for up to 150 concurrent users. The platform effectively visualizes flood risk zones, evacuation routes, and shelter capacities in real time. The findings demonstrate that participatory web-based GIS tools can significantly enhance local disaster readiness and community empowerment. This research contributes to the advancement of inclusive disaster technology and offers a scalable model for implementation in other high-risk regions.